Knowledge and opinions of parents of children hospitalized in hematology/oncology units regarding complementary and alternative medicine - KARAKOÇ, AYŞE (E D P SCIENCES, 2017)
The current study aimed to determine the knowledge and opinions of parents who had children with cancer regarding complementary and alternative medicine. This descriptive study was performed with 145 parents. Data collection was implemented by means of a literature-based questionnaire. Of the parents who were enrolled into the study, 42.1% were aged 36 years or older and 57.2% had primary school education only. A total of 86.9% of the information was gathered from the mothers of the children. All parents preferred CAM therapies for their children's treatment; more than half used herbs as CAM, and 81.4% of the parents who used CAM with held this information from healthcare professionals. All parents had insufficient knowledge about complementary and alternative treatments, including those who had opted out of conventional medicine, but wanted to learn more about them. Therefore, healthcare professionals should improve their knowledge of CAM methods and be able to appropriately enlighten parents while providing an environment in which families can freely discuss information.
Keywords: Child; cancer; parent; complementary and alternative practices; PEDIATRIC ONCOLOGY PATIENTS; CANCER; THERAPIES; POPULATION; PREVALENCE; TURKEY